Microwave-Assisted BiCl3 Catalyzed Synthesis of α-Hydroxyphosphonates - Abdeslem Bouzina; Yousra Ouafa Bouone; Rachida Mansouri; Nour-Eddine Aouf (Chemistry Proceedings)
In this study, we present a straightforward, resource-efficient, and environmentally sustainable approach for the synthesis of α-hydroxyphosphonate derivatives. This synthetic methodology involves the reaction of aromatic aldehydes with triethylphosphite and utilizes microwave irradiation as a source of activation energy and was catalyzed by bismuth chloride III at an amount of 20 mol%. The protocol affords rapid and highly efficient results, yielding α-hydroxyphosphonates in high yields while minimizing reaction times.